Predicting third wave of COVID 19 in Nepal (Journal of Patan Academy of Health Sciences, 2021)
Nepal is experiencing second wave of COVID-19 infection leading to major health impacts and crisis. Despite the development of vaccine against COVID-19 and its wider coverage, many countries have already experienced third wave. After vaccination against COVID-19 antibodies has been seen to be present till eight months in different studies, evidences beyond that is yet to come. Looking at the trends of reinfections and mathematical models for prediction of COVID-19 infection, there is high chances that Nepal will face third wave, and children will be affected more due to unavailability of vaccine for this age group. There is no fixed definite time to detect when the third wave hit. From the health crisis experience during second wave, Nepal should stress on implication of various strategic and evidence-based measures for third wave preparedness and mitigation to minimize the morbidity, post COVID-19 infection complications and mortality.